Design of the hydraulic shock absorbers characteristics using relative springs deflections at general excitation of the bus wheels - Polach P. (Applied and Computational Mechanics, 2010)
The air-pressure-controlled hydraulic shock absorbers of axles’ air suspension are capable of changing their damping forces in dependence on air pressure in air springs. Due to the possibility of improving dynamic properties of all vehicles that use the axles’ air suspension, BRANO a.s., the Czech producer of shock absorbers, developed semi-active air-pressure-controlled hydraulic telescopic shock absorbers. The force-velocity characteristics of the controlled shock absorbers were designed on the basis of relative deflections of the air springs. As a criterion for the design of the optimum characteristics of the controlled shock absorbers the maximum similarity of dynamic responses of multibody models of the SOR C 12 bus for all the considered weights to the dynamic response of the reference multibody model was chosen. Time histories of relative deflections of the axles’ air springs determined during the simulations are compared. Simulations of running over an obstacle with all the wheels were originally chosen (symmetric kinematic excitation of wheels). Verification of the suitability of the designed force-velocity characteristics of the APCSA described in this paper is performed on the basis of the simulations of general kinematic excitation of wheels. Driving on the artificially created test track according to the ŠKODA VÝZKUM methodology was chosen.